Principles for teaching sonography – current status - Bintaro, Sabine; Dietrich, Christoph F.; Potthoff, Andrej (Zeitschrift für Gastroenterologie, 2023)
Since many young medical residents require sonographic skills early on during training, increased attention has been paid to including sonography classes in undergraduate medical education, among both professional societies and medical educators responsible for medical licensing exams. Medical schools worldwide have developed and implemented a variety of ultrasound teaching formats.This article addresses evidence-based solutions to crucial challenges in planning and implementing undergraduate sonography education. In order to achieve a sustainable increase in practical sonographic competence, we suggest small-group classes with sufficient individual hands-on scanning time for each student. We recommend concentrating on a circumscribed topic and teaching it thoroughly and practically rather than superficially outlining a broad subject area. Provided that peer teachers undergo adequate training, student peer teachers are not inferior to physicians as teachers, as far as student satisfaction, theoretical knowledge and practical skills acquisition are concerned. The assessment of acquired practical skills should consist of practical examinations, such as an objective structured clinical examination (OSCE) or a direct observation of procedural skills (DOPS). In contrast to using healthy volunteers as training models, simulation trainers allow the demonstration of pathological findings in authentic sonographic images, with the disadvantages of unrealistically easy image acquisition, as well as the lack of interaction with the patient.
Keywords: undergraduate medical education; ultrasound education; ultrasound simulator; student tutors